Dietary Omega-3 Fatty Acids Promote Arrhythmogenic Remodeling of Cellular Ca(2+) Handling in a Postinfarction Model of Sudden Cardiac Death - Belevych, Andriy E. (Public Library of Science, 2013)
It has been proposed that dietary omega-3 polyunsaturated fatty acids (n-3 PUFAs) can reduce the risk of ventricular arrhythmias in post-MI patients. Abnormal Ca(2+) handling has been implicated in the genesis of post-MI ventricular arrhythmias. Therefore, we tested the hypothesis that dietary n-3 PUFAs alter the vulnerability of ventricular myocytes to cellular arrhythmia by stabilizing intracellular Ca(2+) cycling. To test this hypothesis, we used a canine model of post-MI ventricular fibrillation (VF) and assigned the animals to either placebo (1 g/day corn oil) or n-3 PUFAs (1-4 g/day) groups. Using Ca(2+) imaging techniques, we examined the intracellular Ca(2+) handling in myocytes isolated from post-MI hearts resistant (VF-) and susceptible (VF+) to VF. Frequency of occurrence of diastolic Ca(2+) waves (DCWs) in VF+ myocytes from placebo group was significantly higher than in placebo-treated VF- myocytes. n-3 PUFA treatment did not decrease frequency of DCWs in VF+ myocytes. In contrast, VF- myocytes from the n-3 PUFA group had a significantly higher frequency of DCWs than myocytes from the placebo group. In addition, n-3 PUFA treatment increased beat-to-beat alterations in the amplitude of Ca(2+) transients (Ca(2+) alternans) in VF- myocytes. These n-3 PUFAs effects in VF- myocytes were associated with an increased Ca(2+) spark frequency and reduced sarcoplasmic reticulum Ca(2+) content, indicative of increased activity of ryanodine receptors. Thus, dietary n-3 PUFAs do not alleviate intracellular Ca(2+) cycling remodeling in myocytes isolated from post-MI VF+ hearts. Furthermore, dietary n-3 PUFAs increase vulnerability of ventricular myocytes to cellular arrhythmia in post-MI VF- hearts by destabilizing intracellular Ca(2+) handling.